The Concept Of Environmental Management And Discussing Its Impact On Production/Operations Management (POM) - Thalib, Abbadi Said; Mohamad, Miranti Adiningtyas (Journal Research of Social Science, Economics, and Management, 2024)
This study delves into the concept of environmental management and explores its implications on Production/Operations Management (POM). Environmental management, as a multidisciplinary approach, addresses the sustainable utilization of resources and the minimization of environmental impact in organizational processes. The research investigates the integration of environmental considerations into POM strategies, emphasizing the potential impacts on production efficiency, waste reduction, and overall sustainability. By analyzing relevant literature and case studies, this study aims to provide insights into the symbiotic relationship between environmental management practices and POM, highlighting the potential benefits of aligning production operations with environmentally conscious principles. The findings contribute to a better understanding of how environmental considerations can be strategically incorporated into production processes, fostering a more sustainable and responsible approach to operations management.